Implementation of Medan City Regional Regulation Number 4 of 2014 in the Framework of the Existence of Medan Zoo as a Tourist Attraction in Medan City - Indra, Cindiya Calida (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
In realizing the development of good tourist destinations, it is necessary to improve the quality and quality of these destinations in order to create a good image of the destination in the eyes of visitors and the community. Zoos have great and good tourism potential to be developed into tourist destinations that have an educational function because they provide information to community about the life of wild animals, and can interact directly with animals and the function of conservation as a means of protection and preservation of nature, animals and plants. The type of research used in this study is a qualitative research type with five sources. The results of the study indicate that the implementation of the Medan City Regional Regulation Number 4 of 2014 in the context of the existence of the Medan Zoo as a tourist attraction in the city of Medan during the new normal of this pandemic has been effective. The forms of implementation of existence carried out are: 1) Development of facilities and infrastructure which includes intensive cleaning of the zoo environment, checking the condition of animals, sterilizing areas, adding children's playgrounds and repairing all facilities damaged due to closure during the Covid-19 pandemic. 2) Adding facilities such as providing a place to wash hands, distributing sanitizers for free and equipment for checking body temperature. 3) Implementation of new rules and regulations, such as wearing masks, maintaining cleanliness, maintaining distance, making price promotions and limiting the number and hours of tourist visits. 4) form a partnership with partners to raise funds for additional facilities and animal protection needs at the Medan Zoo.